2002
DOI: 10.1182/blood.v99.2.531
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the recombination-activating genes in extrafollicular lymphocytes but no apparent reinduction in germinal center reactions in human tonsils

Abstract: V(D)J recombination in lymphocytes is (Ig) and T-cell receptor (TCR) genes is mediated by the products of 2 recombinationactivating genes (RAG1 and RAG2) which recognize specific recombination signal sequences (RSS) flanking the V, D, and J gene segments. 1,2 The RAGs are transiently and coordinately expressed during B-cell and T-cell ontogeny in bone marrow and thymus, respectively. [3][4][5] Upon completion of V(D)J rearrangement, RAG expression is shut down. 3 IgM-expressing immature bone marrow B cells rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…The expression of RAG in secondary and tertiary lymphoid organs has been debated partly due to divergent findings (15)(16)(17)(18)(19)38). Even among studies that have identified expression of RAGs in secondary lymphoid tissues, expression has been reported in Ignegative cells, consistent with centroblasts as observed here (17), and also in centrocytes (38).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The expression of RAG in secondary and tertiary lymphoid organs has been debated partly due to divergent findings (15)(16)(17)(18)(19)38). Even among studies that have identified expression of RAGs in secondary lymphoid tissues, expression has been reported in Ignegative cells, consistent with centroblasts as observed here (17), and also in centrocytes (38).…”
Section: Discussionsupporting
confidence: 48%
“…Evidence of revision in man has been observed in autoimmunity and malignant human tissues (15,16), though it has not been universally accepted to be part of normal B cell physiology. Expression of RAGs, which would be essential for revision, has been observed in germinal centers by some groups but not others (15,17,18). Data from a transgenic mouse model suggested that RAGs are not re-expressed in the periphery but that expression may be retained by recent emigration from the bone marrow (19).…”
Section: P Recursors Of Iga Plasma Cells (Pc)mentioning
confidence: 98%
“…These observations underscore the continuing uncertainty regarding the expression and function of RAG in peripheral B cells. Furthermore, B cells expressing RAG have also been observed outside of GCs in immunized mice (52) and in extrafollicular areas of human tonsil (53). Detection of light chain rearrangement products in RAG-expressing B cells in the periphery clearly suggested that receptor editing or revision may occur in B cells beyond the immature stage (9,(54)(55)(56).…”
Section: Discussionmentioning
confidence: 83%
“…TdT + cells have been identified in the human tonsil near the fibrous scaffold (8)(9)(10)(11). However, they have yet to be characterized with regard to origin, hematopoietic lineage, or function.…”
Section: Expression Of T Cell Development-associated Genes In Putativmentioning
confidence: 99%
“…Similarly, CD5 + CD7 + CD3 -cells have been identified in neonatal intestine, and PTCRA, TdT (also known as DNTT), and RAG2 mRNA can be detected in whole lysates of these tissues (7); yet, whether or not CD34 + T cell progenitors reside there is unclear. Finally, several reports have identified TdT + cells in extrafollicular zones of the human tonsil near fibrous scaffolding (8)(9)(10)(11). However, little is known about the function or phenotype of these cells.…”
Section: Introductionmentioning
confidence: 99%